When parasitoids deal with the spatial distribution of their hosts: consequences for both partners. (17th April 2018) - Louâpre, Philippe; Le Lann, Cécile; Hance, Thierry
Abstract: Insect parasitoids developing inside hosts face a true challenge: hosts are scattered in the field and their localization and selection require the use of complex and sometime confusing information. It was assumed for a long time that small‐brained organisms like parasitoids have evolved simple and efficient behavioral mechanisms, leading them to be adapted to a given ecological situation, for example, the spatial distribution of hosts in the habitat. However, hosts are not static and their distribution may also vary through generations and within the life of parasitoid individuals. We investigated if and how parasitoids deal with such a spatial complexity in a mesocosm experiment. We used the Aphidius rhopalosiphi / Sitobion avenae parasitoid/host system to investigate if parasitoid females experiencing different host aggregation levels exhibit different foraging behaviors independently of the number of hosts in the environment. We showed that A. rhopalosiphi females exploited hosts more intensively both within and among patches at higher host aggregation levels. We discussed the adaptiveness of such behaviors in the light of evolution and biological control.